Dementia in late-onset epilepsy: The Atherosclerosis Risk in Communities study. (15th December 2020) - Johnson, Emily L.; Krauss, Gregory L.; Kucharska-Newton, Anna; Albert, Marilyn S.; Brandt, Jason; Walker, Keenan A.; Yasar, Sevil; Knopman, David S.; Vossel, Keith A.; Gottesman, Rebecca F.
Abstract : Objective: To determine the risk of dementia after the development of late-onset epilepsy. Methods: We used data from the Atherosclerosis Risk in Communities (ARIC) cohort study, which started in 1987 to 1989 with 15, 792 mostly Black and White men and women from 4 US communities. We identified late-onset epilepsy (LOE; seizures starting at age 67 or later) from linked Medicare claims data. We used a Cox proportional hazards regression model to evaluate associations between LOE and dementia through 2017 as ascertained from neuropsychological testing, interviews, and hospital discharge surveillance, and we used multinomial logistic regression to assess the risk of dementia and mild cognitive impairment in the subset with full neuropsychological assessments available. We adjusted for demographics and vascular and Alzheimer disease risk factors. Results: Of 9, 033 ARIC participants with sufficient Medicare coverage data (4, 980 [55.1%] female, 1993 [22.1%] Black), 671 met the definition of LOE. Two hundred seventy-nine (41.6%) participants with and 1, 408 (16.8%) without LOE developed dementia ( p < 0.001). After a diagnosis of LOE, the adjusted hazard ratio for developing subsequent dementia was 3.05 (95% confidence interval 2.65–3.51). The median time to dementia ascertainment after the onset of LOE was 3.66 years (quartile 1–3, 1.28–8.28 years). Interpretation: The risk of incident dementia is substantially elevated in individuals with LOE. Further work is needed to explore causes for the increased risk of dementia in this growing population.